2008
DOI: 10.1108/09615530810879738
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of heat transfer enhancement in a double pipe heat exchanger with porous fins

Abstract: PurposeThe aim is to study numerically the heat transfer enhancement in a double pipe heat exchanger by using porous fins attached at the external wall of the inner cylinder.Design/methodology/approachThe Brinkman‐Forchheimer extended Darcy model is used in the porous regions. The differential equations subjected to the boundary conditions are solved numerically using the finite volume method. Numerical calculations are performed for a wide range of Darcy number (10−6≤Da≤10−1), porous fins height (0≤Hp≤1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 11 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…Besides that viscous shear at the boundary wall, variable porosity as well as thermal dispersion also plays a major role in the model. In many applications, the Brinkman-extended Darcy and Brinkman–Forchheimer-extended Darcy 3638 have also been used to estimate fluid and heat flow through porous media especially for high Darcy number.…”
Section: Flow and Heat Transfer Analysis Through Porous Mediamentioning
confidence: 99%
“…Besides that viscous shear at the boundary wall, variable porosity as well as thermal dispersion also plays a major role in the model. In many applications, the Brinkman-extended Darcy and Brinkman–Forchheimer-extended Darcy 3638 have also been used to estimate fluid and heat flow through porous media especially for high Darcy number.…”
Section: Flow and Heat Transfer Analysis Through Porous Mediamentioning
confidence: 99%
“…They concluded that the rate of heat transfer was increased when the porous media structures were in a staggered arrangement. Kahalrras and Targui 10 studied numerically the enhancement of heat transfer in a double pipe heat exchanger, where porous fins were installed at the outer surface of the inner pipe. They found an improvement in the heat transfer rate in comparison with the case of the nonuse of porous fins.…”
Section: Introductionmentioning
confidence: 99%
“…Kiwan introduced a new parameter called S H by using Rayleigh and Darcy numbers, thermal conductivity ratio, and length thickness ratio and found that increasing S H by increasing either Darcy or Rayleigh numbers increases the heat transfer rate from the fin. Kahalerras and Targui investigated the performance of a double pipe heat exchanger fitted with porous fins. The results showed that the insertion of porous fins may change the flow pattern depending on their permeability, height, and spacing.…”
Section: Introductionmentioning
confidence: 99%